Die Gogarene im ausgehenden fünften Jahrhundert. Politische Handlungsspielräume und religiöser Pragmatismus - Schleicher, Frank (Anabasis. Studia Classica et Orientalia, 2017)
The Transcaucasian kingdoms of the fifth century are shaped by weak central powers, the increasing self-confidence of the local dynasties and the claim to power of the big neighbours that became increasingly more intense, especially the Sasanians. The regional rulers were able to act more and more politically independent. In Persarmenia, the kingdom had already been removed under their pressure in 428, but even where it continued to exist, it never exerted actual power over all aristocratic families. An impressive example is the Gogarene. This princedom was ruled by a powerful autonomous dynasty, even though it belonged nominally to the kingdom of Iberia. This contribution shows which scopes of action Varsk᾽en, one of these dynasts, was able to use to consolidate and enlarge his power. The conversion to the Persian official religion earned Varsk ᾽en a bad reputation which makes it extremely hard to judge his political and religious motives. The examination shows that these were far from unusual or extreme but corresponded to the possibilities of the time. To gain the largest possible independence from the Iberian king, Varsk᾽en stuck to the Persians. Through the ascent within the ‘Persian’ hierarchy, he also strengthened his own power in the region. Nevertheless, he never went as far as oppressing his own Christian subjects. Religious beliefs appear to be to him a matter of the family, not a matter of the state.